2020
DOI: 10.3390/polym12030585
|View full text |Cite
|
Sign up to set email alerts
|

Improved Properties of Metallocene Polyethylene/Poly(ethylene terephthalate) Blends Processed by an Innovative Eccentric Rotor Extruder

Abstract: In this investigation, metallocene polyethylene (m-PE) was melt blended with poly(ethylene terephthalate) (PET) with an effort to achieve improved mechanical properties using a novel eccentric rotor extruder (ERE) without the addition of any compatibilizers. The phase morphology, rheological properties, crystallization behavior, and mechanical properties of the fabricated blends were carefully studied to explore the effect of the elongational flow field on the dispersion and mixing of PET in the m-PE matrix an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…It was revealed that the application of the continuous elongational flow results in better distribution of PET in LLDPE matrix with a certain compatibilizer, exhibiting 226% and 394% improvements in impact strength and elongation at break, respectively. More recently, they successfully improved the properties of metallocene polyethylene (m-PE)/PET blends using ERE [ 42 ]. Improvements in both particle/particle size distribution of PET in m-PE matrix were found as compared with the shear flow dominated process in TSE.…”
Section: Applications Of Elongational Flow Dominated Plasticizing and Convey Devicesmentioning
confidence: 99%
“…It was revealed that the application of the continuous elongational flow results in better distribution of PET in LLDPE matrix with a certain compatibilizer, exhibiting 226% and 394% improvements in impact strength and elongation at break, respectively. More recently, they successfully improved the properties of metallocene polyethylene (m-PE)/PET blends using ERE [ 42 ]. Improvements in both particle/particle size distribution of PET in m-PE matrix were found as compared with the shear flow dominated process in TSE.…”
Section: Applications Of Elongational Flow Dominated Plasticizing and Convey Devicesmentioning
confidence: 99%
“…Therefore, a high content of elastomer loading is required to achieve a significant increase in toughness, resulting in a sharp decrease in the tensile strength and modulus of PLA composites . Moreover, due to the poor interfacial adhesion between polymer matrix and elastomers, compatibilizers are added to enhance interfacial properties in previous studies, , which sacrificed the degradability of the blends to some extent.…”
Section: Introductionmentioning
confidence: 99%